Imperative and Dispositive Norms in Legal Regulation of Genetic Research in Russia. / Normas imperativas y dispositivas en la regulación legal de la investigación genética en Rusia. - VALER’EVICH VORONIN, MAXIM; VLADIMIROVNA ZAKHAROVA, MARIA; VLADIMIROVNA KOZLOVA, NATALIIA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the analysis of diverse utilization varieties of regulatory framework at adjusting genetic techniques and global legal practice research. Internal determinants of the development of national systems and external universal laws of legal transformation influence the evolution of views of the professional community of lawyers in Russia and in foreign countries, regarding the choice of dispositive or mandatory ways of regulating genetic research. The discussion on a number of legal institutions and on the choice of effective methods and forms of legal regulation in the world and Russian legal practice continues. RESUMEN El artículo está dedicado al análisis de diversas variedades de utilización del marco regulatorio para ajustar las técnicas genéticas y la investigación de la práctica legal global. Los determinantes internos del desarrollo de los sistemas nacionales y las leyes universales externas de transformación legal influyen en la evolución de los puntos de vista de la comunidad profesional de abogados en Rusia y en países extranjeros, con respecto a la elección de formas obligatorias o dispositivas para regular la investigación genética. Continúa el debate sobre una serie de instituciones jurídicas y sobre la elección de métodos y formas eficaces de regulación jurídica en el mundo y la práctica jurídica rusa.